Pola Kepemimpinan Kepala Sekolah dalam membentuk Multicultural Personality di SDN 1 Desa Balun - Putri, Mutammimah Putri; Faisal Rahmatullah; Muhammad Naufal Wavi (STAI Ihyaul Ulum Gresik, 2023)
SDN I Balun is a school located in Balun Village, Turi District, Lamongan Regency. This school is unique because its students come from three different religions: Islam, Christianity and Hinduism, and many families are even multi-religious. The leadership style applied by the principal in forming a multicultural personality at SDN 1 Balun Village is a democratic-multicultural leadership pattern. The driving factors for forming a multicultural personality at SDN 1 Balun Village are the high state of multiculturalism in the Balun Village community and the motivation and awareness of the SDN 1 Balun Village school regarding the urgency of forming a multicultural personality for students. Meanwhile, the inhibiting factors are the different levels of intelligence of students, the lack of adequate facilities and infrastructure, and the lack of slogans/posters about tolerance